Pengembangan Sistem Informasi Pelayanan Pemesanan Berbasis Web Menggunakan Metode Extreme Programming Pada Usaha Kecil Menengah - Destriana, Rachmat; Sugiyani, Yani; Yudi Priyanggodo, Dyas; Prasetyoadi, Erwin (Jurnal Teknik, 2024)
Kedai Wildan is  a  restaurant that is  often visited. Not  a  few restaurants are overwhelmed to serve customers when it's busy. Customers also feel uncomfortable if the service in the wildan stall is not optimal. One of the problems is the menu ordering system which still uses the manual method and customers must come to the location to be able to order the existing menu. This was considered ineffective and inefficient considering the limited number of employees which was disproportionate to the hectic number of visitors who came. So we need a system that can make it easier to  order menus at  Kedai Wildan. Therefore, a  website-based food  and beverage menu ordering system was created to make it easier for customers and employees. The method used is the data collection method which consists of the observation method, the interview method, the literature study method, and includes the analysis method using the PIECES method, the system development method using the extreme programming method, and the design is carried out using the Unified Modeling Language (UML) method. To test the system using Black Box Testing, namely the login process, managing menu data, and viewing order invoices. With this menu ordering information.